1998
DOI: 10.1002/(sici)1096-8628(19981204)80:4<356::aid-ajmg10>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Absence of correlation between skewed X inactivation in blood and serum creatine-kinase levels in Duchenne/Becker female carriers

Abstract: The pattern of X inactivation in lymphocyte DNA was investigated in 107 Duchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD) carriers (102 asymptomatic and 5 manifesting carriers) and 117 normal female controls of different ages, with the aim: a) to analyze the pattern of X inactivation in blood DNA of a large number of DMD/BMD carriers as compared to normal female controls; b) to determine if there is a decrease in serum creatine kinase (CK) levels with age in obligate DMD/BMD carriers; c) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 40 publications
(50 reference statements)
0
17
0
Order By: Relevance
“…Skewed XCI, with preferential inactivation of the wild allele, is a possible mechanism to explain symptoms in DMD-manifesting carriers. The non-perfect correlation between skewed inactivation in blood lymphocytes and the corresponding phenotype -previously reported -should have several explanations: investigation of a non-homogeneous group of carriers (DMD vs BMD, only manifesting or non-manifesting carriers) (13,18,22), only young carriers (12), lack of discrimination between mutant and normal alleles (4,13,19,21), presence of autosomal alleles able to modify the phenotype, as the osteopontin promoter (SPP1) polymorfism (23,25), biochemical normalization in muscles of DMD carriers (26).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Skewed XCI, with preferential inactivation of the wild allele, is a possible mechanism to explain symptoms in DMD-manifesting carriers. The non-perfect correlation between skewed inactivation in blood lymphocytes and the corresponding phenotype -previously reported -should have several explanations: investigation of a non-homogeneous group of carriers (DMD vs BMD, only manifesting or non-manifesting carriers) (13,18,22), only young carriers (12), lack of discrimination between mutant and normal alleles (4,13,19,21), presence of autosomal alleles able to modify the phenotype, as the osteopontin promoter (SPP1) polymorfism (23,25), biochemical normalization in muscles of DMD carriers (26).…”
Section: Discussionmentioning
confidence: 93%
“…Clinical manifestations in DMD carriers is believed to depend on the amount of dystrophin expressed, that in turn depends on the pattern of X-chromosome inactivation (XCI); however, previous studies on the XCI patterns in manifesting carriers did not find a perfect correlation with the clinical manifestations (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…However, results concerning the use of XCI as a prognostic marker are controversial. While some studies found that the great majority of symptomatic cases exhibited skewed profiles [20-22] others found that XCI is not a reliable measure to predict whether carrier female will develop symptoms [6,10,24]. Most women in the normal population present a random XCI pattern in peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most frequently reported mechanism to provoke symptoms in DMD carriers is skewed X-inactivation, favouring the expression of the X chromosome with the DMD mutated allele [8,20-22]. Although some studies suggest the use of X-inactivation analysis for prognostic purposes, the results of different reports are controversial [21,23,24]. …”
Section: Introductionmentioning
confidence: 99%
“…XCI in muscle was random in all manifesting carriers investigated. Furthermore, no correlation was found between XCI and phenotype measured as serum creatine kinase levels (Sumita et al 1998).…”
Section: X-linked Disorders Usually Associated With Random XCI and Vamentioning
confidence: 92%